2012
DOI: 10.1038/onc.2012.41
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α9β1 promotes malignant tumor growth and metastasis by potentiating epithelial-mesenchymal transition

Abstract: The integrin α9β1 binds a number of extracellular matrix components to mediate cell adhesion, migration and tissue invasion. Although expressed in variety of normal human cells including endothelium, it is also expressed in cancer cells. We have previously shown that α9β1 binds VEGF-A to facilitate angiogenesis, an important component of the tumor microenvironment. Since α9β1 induces accelerated cancer cell migration, we wished to determine what role it played in cancer growth and metastasis. In this study we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 39 publications
1
39
0
Order By: Relevance
“…22 Upregulated expression of αvβ3 is also observed in TGF-β-induced EMT in murine mammary epithelial cells. 23 Moreover, colon cancer cells transfected with α9β1 display an EMT phenotype, 24 and pancreatic cancer cells plated on collagen I show EMT-like change mediated through integrin α2β1. 25 …”
Section: Introductionmentioning
confidence: 99%
“…22 Upregulated expression of αvβ3 is also observed in TGF-β-induced EMT in murine mammary epithelial cells. 23 Moreover, colon cancer cells transfected with α9β1 display an EMT phenotype, 24 and pancreatic cancer cells plated on collagen I show EMT-like change mediated through integrin α2β1. 25 …”
Section: Introductionmentioning
confidence: 99%
“…Hedgehog, Notch, Wnt, and transforming growth factor (TGF)-β are capable of initiating EMT via up-regulation of a group of transcription factors [19] and a large number of laminins [20] and integrins [21] related to EMT have been identified. However, the precise mechanisms of EMT/MET remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found evidence for an a9b1-b-catenin-E-cadherin complex that dissociated upon a9b1 integrin-ligand interaction and subsequent Src and bcatenin phosphorylation. Further, investigation of small cell lung carcinoma samples from 15 patients showed that high expression of a9b1 could be a prognostic indicator of poor survival and the average survival time for patients with high a9b1 was significantly reduced (Gupta et al, 2012). This finding is important to replicate with a larger set of patients.…”
Section: A9b1 In Cancermentioning
confidence: 88%
“…a9b1 has recently been implicated in epithelial-mesenchymal transition (EMT), independently of the known EMT inducer, TGF-b (Gupta et al, 2012). The authors found evidence for an a9b1-b-catenin-E-cadherin complex that dissociated upon a9b1 integrin-ligand interaction and subsequent Src and bcatenin phosphorylation.…”
Section: A9b1 In Cancermentioning
confidence: 96%